Analisis Dampak Perubahan Iklim Terhadap Hak Pada Manusia - Faturohman Faturohman; Lucki Hidayanto; Muhamad Fahruroji (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Global warming occurs due to changes in weather patterns, rising sea levels, and also very extreme weather phenomena. These human rights are in the form of rights to life and health, where climate change can directly threaten the rights to life and health of humans. An increase in global temperatures can also cause the frequency and intensity of heat waves to increase, which can cause deaths and heat-related illnesses. In addition, changes in rainfall patterns can cause extreme flooding and drought, resulting in physical damage, disease, and loss of life. Water-borne and vector-borne diseases, such as malaria and dengue, are also expected to increase with climate change. Not only that right but there is also the right to food, where if there is a change in the climate, this can affect global food security. Changing weather patterns, such as increased frequency and intensity of droughts, floods, and storms, can damage agricultural land and reduce crop yields. This threatens the right to food, especially for communities that depend on subsistence agriculture. Additionally, rising temperatures and changing rainfall patterns can affect crop productivity and livestock health, impacting food supply and food prices.